FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PRAKTIK TRANSFER PRICING - Rayhan Fachrizal; Susanto Salim (Jurnal Paradigma Akuntansi, 2023)
The purpose of this research is to obtain an empirical evidence about the influence of tax, bonus mechanism, and tunneling incentive on the decision of transfer pricing practice on manufacturing company listed in BEI at the periode of 2018-2020 There are 81 sample that used in this particular research with purpose sampling collection method. Data processing technique uses logistic regression analysis assisted by Microsoft Excel 2019 and SPSS version 26 software. The result of this research stated that tax and bonus mechanism doesn’t have a significant effect on the firm decision of transfer pricing, while tunneling incentive able to give a significant effect on the firm decision of transfer pricing practice in manufacturing company that listed in BEI periode 2018-2020.